Thrombocytopenia in patients with Plasmodium vivax in Colombia is associated with anti-phosphatidylserine autoantibodies and IL-6, IFNγ, IL-10 and TGF-β. - María Camila Velasco-Pareja; Catalina Tovar-Acero; Miriam E Cantero Guevara; Ana Rodriguez; Juan Rivera-Correa; María Fernanda Yasnot-Acosta (PLoS Neglected Tropical Diseases, 2025)
Plasmodium vivax is the most widely distributed human protozoan in the world. It is a causative agent of malaria, with thrombocytopenia being a frequent complication. This study aimed to evaluate the effect of P. vivax infection on plasma cytokine/chemokine levels and anti-phosphatidylserine (anti-PS) autoantibodies, to explore their potential role in thrombocytopenia during P. vivax malaria in Córdoba, Colombia. We included patients with P. vivax malaria and thrombocytopenia (MT); patients with malaria without thrombocytopenia (M) and healthy controls (HC). Plasma cytokines/chemokines (IL-2, IL-4, IL-1β, TNF-α, IL-17A, IL-6, IL-10, IFNγ, IL-12p70, TGF-β1/IP-10, MCP-1, IL-8) were quantified. Evaluation of autoantibodies was performed by ELISA, using phosphatidylserine (PS) as the antigen. IFNγ, IL-6, and IL-10 were found to increase in the MT group (P < 0.05), whereas TGF-β1 was increased in the M group (P < 0.0001). Anti-PS antibody levels were also higher in the MT group and showed a negative correlation with platelet counts. These findings suggest that thrombocytopenia in P. vivax malaria may result from autoantibodies targeting phosphatidylserine on activated platelets, driven by a pro-inflammatory cytokine imbalance, with TGF-β1 potentially exerting a protective effect.